Criminal Responsibility for Corruption Crime Committed in Concursus. - Annisa; Ali Johardi Wirogioto (Jurnal Kajian Ilmu Kepolisian dan Anti Korupsi, 2024)
A corruption is still a serious problem, especially within the scope of the state civil apparatus (ASN). criminal acts of corruption can not only be committed individually but also concursus or jointly. related to the criminal act of corruption committed concursus is the criminal liability received by the perpetrators of the criminal act of corruption concursus. Also the types of penalties received by convicts of corruption concursus. This research aims to find out how the criminal liability of corruption committed in concursus and how the types of punishment for the perpetrators of the criminal act of corruption committed in concursus. the research method used is normative juridical, literature study, descriptive analysis, using a theoretical framework and conceptual framework and legal sources relevant to the research. The results of the research on criminal liability for corruption crimes committed in concursus are in accordance with juridical considerations, but in non-juridical terms it is still not commensurate with the actions taken by the perpetrators of corruption crimes. the types of penalties received by convicts also do not provide justice to convicts involved in concursus corruption cases. Therefore in the case of corruption crimes which are extra ordinary crimes, if the granting of leniency is easy, the deterrent effect expected by criminal justice will not exist. then to realize justice for the whole granting of leniency in corruption crimes must pass a difficult stage.